CONCEPT AL-'ADAH MUHAKKAMAH IN TRADITION BAKAMPUONG UGHANG PRA WALIMATUL ‘URSY IN KAMPAR RIAU COMMUNITY - Muhammad Fazli; Ismail Ismail (Universitas Islam Negeri Ar-Raniry, 2023)
The background of this research is the existence of a very unique tradition in Merangin Village, Kuok District, Kampar Regency, Riau Province to hold walimatul 'ursy, which is the name of the tradition, the bakampuong ughang tradition. The bakampuong ughang tradition is carried out a week before the implementation of the walimatul 'ursy which aims to raise funds so that the bride and groom can also hold a walimatul 'ursy party. The main problems in this study are how the implementation and objectives of the bakampuong ughang tradition and the factors that cause the persistence of the bakampuong ughang tradition, what are the implications or impacts of the bakampuong ughang tradition on the lives of Muslim communities in Merangin Village, Kuok District, Kampar Regency, Riau Province and how is the review 'urf on the implications or impacts of the bakampuong ughang tradition. Based on the results of the research that the writer has done, the writer can conclude that the bakampuong ughang tradition is a habit of the people of Merangin Village, Kuok District, Kampar Regency, Riau Province before the walimatul 'ursy event takes place. The implications or impacts of the bakampuong ughang tradition are: first, the good and bad impacts. The Qur'an and Hadith stipulate that the implementation of walimatul 'ursy is sunnah muakkad, meaning that it is permissible to do it and it is permissible not to do it.